Inducing variety: A theory of innovation contests - Igor Letina; Armin Schmutzler (University of Zurich, Department of Economics, 2019)
This paper analyzes the design of innovation contests when the quality of an innovation depends on the research approach, but the best approach is unknown. Inducing a variety of research approaches generates an option value. We show that suitable contests can induce such variety. The buyer-optimal contest is a bonus tournament, where suppliers can choose only between a low bid and a high bid. This contest implements the socially optimal variety for a suitable parameter range. Finally, we compare the optimal contest to scoring auctions and fixed-prize tournaments.
Keywords: L14; L22; L23; 330; contests; tournaments; auctions; diversity; innovation; procurement